The Roman Empire and the New Testament an essential guide - Carter, Warren 1955- (Nashville Abingdon Press, 2006)
An indispensable introduction to Roman society, culture, law, politics, religion, and daily life as they relate to the study of the New Testament.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books